Communication Adaptation of International Students in Dealing with Culture Shock in Medan City - Ikke Nadia; Hasan Sazali (Ali Institute of Research and Publication, 2026)
This study explores how international students at Universitas Muhammadiyah Sumatera Utara (UMSU) navigate cultural differences and adapt to a new social environment while experiencing culture shock. The increasing mobility of international students in Indonesian higher education has created various intercultural communication challenges, particularly during the adaptation process. This research employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving international students, local students, lecturers, and dormitory administrators. The findings indicate that international students experienced culture shock related to language barriers, differences in social norms, communication styles, and everyday cultural practices. To cope with these challenges, they engaged in interpersonal and intercultural interactions with local students and members of the academic community. Adaptation strategies included language adjustment, environmental observation, the use of translation technologies, and participation in social activities. The findings also suggest that support from local students, lecturers, dormitory environments, and campus facilities contributed to students’ adaptation processes. These experiences can be understood through the perspective of Communication Accommodation Theory (CAT), particularly in terms of communication adjustments undertaken to facilitate interaction and social acceptance while maintaining aspects of their original cultural identity.